Pendeteksi Kerusakan Docucenter 235 Pada Perangkat Mobile dengan Metode Certainty Factor - Felman Ndruru (Graha Mitra Edukasi, 2024)
Docucenter 235 is one of the products from Xerox Corporation that has the advantage of being able to perform many functions. Docucenter 235 can do photocopying, printing, scanning, i-fax, walk up fax, and network fax. According to PT Astragraphia, Tbk as a distributor of this machine in Indonesia has sold more than 3000 units. The need to reproduce documents is very important, therefore the role of docucenter 235 is needed. Docucenter 235 is a photocopier made by Xerox Corporation, but once there are problems such as troubleshooting which results in the results of copying being less than optimal and the processing time becomes slower. The Certainty Factor method is a method in expert systems that is suitable for knowing the certainty or lack of possibility in measuring something, for example, diagnosing diseases and damage. In one calculation, this method can only process 2 data. Therefore, the accuracy of the calculation data with this method can be maintained. This is the reason the author chose to use the Certainty Factor method rather than other methods in this research. The purpose of this study is to detect damage to the docucenter 235 machine that requires trobelshoot or damage. The results of the implementation of the built expert issued output results based on the calculation of the Certainty factor method on damage detection has a percentage of 85% confidence level.